Application of information technology for the evaluation of public science and technology organizations - Anh, Pham Quynh; Ha, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The purpose, process and evaluation criteria of S&T organizations are specified in the Law on Science and Technology 2013 and Circular 18/2019/TT-BKHCN. However, the current assessment is facing many difficulties, especially, the stages in the evaluation process are being done manually, which is time consuming and costly. Therefore, the scale of investigation and evaluation of S&T organizations has not been comprehensive, and difficult to realize evaluation purposes in order to effectively and promptly serve the management of the state. Therefore, the application of information technology to support the assessment of S&T organizations is necessary. In the framework of this article, the authors introduce the database and management software serving the assessment of S&T public institutions in Vietnam. Information will be updated online annually by S&T organization, on a large scale, the validity of information is guaranteed. The evaluation process is computerized to the maximum, resources are saved. Code: 20111201